A Two-Way Proteome Microarray Strategy to Identify Novel Mycobacterium tuberculosis-Human Interactors - Cao, Tingming; Lyu, Lingna; Jia, Hongyan; Wang, Jinghui; Du, Fengjiao; Pan, Liping; Li, Zihui; Xing, Aiying; Xiao, Jing; Ma, Yu; Zhang, Zongde (Frontiers in Cellular and Infection Microbiology, 2019)
Tuberculosis (TB) is still a serious threat to human health which is caused by mycobacterium tuberculosis (Mtb). The main reason for failure to eliminate TB is lack of clearly understanding the molecular mechanism of Mtb pathogenesis. Determining Mtb interacted proteins in human enables us to characterize the mechanism and identify potential molecular targets for TB diagnosis and treatment. However, experimantally systematic Mtb interactors are not readily available. In this study, we performed an unbiased, comprehensive two-way proteome microarray based approach to systematically screen global Mtb interactors in human and determine their binding partners of Mtb effectors. Our results, for the first time, screened 84 potential Mtb interactors in human. Bioinformatic analysis further highlighted these protein candidates might engage in a wide range of cellular functions such as activation of DNA endogenous promoters, transcription of DNA/RNA and necrosis, as well as immune-related signaling pathways. Then, using Mtb proteome microarray followed His tagged pull-down assay and Co-IP, we identified one interacting partner (Rv0577) for the protein candidate NRF1 and three binding partners (Rv0577, Rv2117, Rv2423) for SMAD2, respectively. This study gives new insights into the profile of global Mtb interactors potentially involving in Mtb pathogenesis and demonstrates a powerful strategy in the discovery of Mtb effectors.